Blood Lipid Profile in Acute Coronary Syndrome and Chronic Stable Angina Patients - Parvin, T; Rahman, MH; Ferdousi, S; Shahnaz, A; Mahal, M; Ahmed, SF; Ferdous, BA; Hussain, DAS (Bangladesh Journal of Medical Biochemistry, 2015)
This study was designed to compare the blood lipid profile and conventional cardiovascular risk factors in patients with acute coronary syndrome (ACS) and chronic stable angina (CSA). A total of 110 patients, 55 of which were of ACS and 55 with chronic stable angina (CSA) who underwent coronary angiography in the Department of Cardiology, BSMMU, Dhaka were enrolled for the study. Lipid profile and age, sex, diabetes mellitus, hypertension, hyperlipidemia, smoking habit, family history of premature coronary artery diseases (CAD) of the patients were recorded and compared. Mean±SD age of the studied patients was 52.2±10 years. Prevalence of diabetes mellitus (p<0.05) and hypertension (p <0.05) was significantly higher in patients with CSA than that with ACS. Frequency of hyperlipidemia, smoking habit and family history of CAD was similar between groups. Patients with CSA had significantly higher triple vessel diseases (TVD) (p < 0.001) and significantly lower high-density lipoprotein cholesterol (HDLc) (p < 0.05) compared to that of patients with ACS. ACS patients had significantly higher single vessel diseases (SVD) (p <0.001) compared to that of CSA but the distribution of low-density lipoprotein cholesterol (LDLc), total cholesterol and triglycerides were variable between groups. This study showed that CSA patients had substantially higher frequency of having some CVD risk factors with alteration in certain lipid profile parameters and higher number of triple vessels disease than patients with ACS. This might aid in selecting appropriate criteria for angiographic evaluation and better management of patients with coronary artery diseases. DOI: http://dx.doi.org/10.3329/bjmb.v7i2.22413 Bangladesh J Med Biochem 2014; 7(2): 52-56